REPRESENTATION OF WISDOM IN THE BOOK OF PROVERBS WRITTEN BY SOLOMON - Marudut Bernadtua Simanjuntak (Prosiding Seminar Nasional Bahasa, Sastra, dan Seni (Sesanti), 2019)
This article aims to describe the book of Proverbs for how someone gets wisdom, which the ability to understand everything clearly and use knowledge to overcome a problem. The problem in this study is how verses in the Book of Proverbs can represent wisdom that aims to teach someone to understand each teaching. This research is a qualitative research using descriptive method. The data are taken from The Book of Proverbs written by Solomon. Data collection techniques are reading analysis and documentation. This study uses three steps of work, they are (1) providing data; (2) data analyzing; and (3) presenting the results of the data analysis. This study uses pragmatic theory. The results of this study indicate that verse fragments in articles taken from the Book of Proverbs can teach someone to have wisdom, that wisdom can direct people into discipline, happiness and achievement of success.